Analyzing the Relationship between Economic Indicators and Profitability: A Case Study of NIC Asia Bank Limited, Nepal - Bhatt, Sahadev (Bhairahawa Campus Journal, 2024)
This study explores the relationship between economic indicators and profitability, focusing on NIC Asia Bank Limited, a prominent commercial bank in Nepal. The research aims to analyze historical trends and assess the impact of GDP growth rate, inflation rate, interest rates, and Money Multiplier (M2) on the bank's profitability metrics, specifically return on assets (ROA). Using secondary data from 2018/19 to 2022/23, the study employs statistical methods, including correlation analysis to quantify these relationships. Findings indicate that economic indicators significantly influence NIC Asia Bank's profitability, with interest rates showing a moderate positive correlation with ROA, while inflation and Money Multiplier exhibit complex dynamics impacting bank performance. The insights gained offer valuable recommendations for strategic decision-making, risk management, and policy formulation to enhance the bank's profitability and resilience in a dynamic economic environment. The study contributes to the broader understanding of the interplay between economic conditions and financial performance in the banking sector.